Caricature and Hyperbole in Preservice Teacher Professional Development for Diversity. (July 2016) - Pollock, Mica; Bocala, Candice; Deckman, Sherry L.; Dickstein-Staub, Shari
Professional development (PD) "for diversity" aims to prepare teachers to support students from varying backgrounds to succeed, often in under-resourced contexts. Although many teachers invite such inquiry as part of learning to teach, others resist "diversity" inquiry as extra to teaching, saying they cannot "do it all." In this article, we discuss how preservice teachers at times caricature the requests of PD for diversity, hearing the task as a call to undertake superhuman tasks and to be people other than who they are. We argue that these caricatures require direct acknowledgment by both preservice teachers and teacher educators working in diverse contexts.